FAKTOR FAKTOR YANG MEMPENGARUHI ENVIRONMENTAL PERFORMANCE PADA PERUSAHAAN SEKTOR INDUSTRI DI INDONESIA TAHUN 2018-2022 - Hesniati, Hesniati; Steven, Steven (LPPM STIE Muhammadiah Bandung, 2024)
The natural resource-based view theory approach is an issue that is being paid attention to by academic circles, namely that a company's competitiveness comes from the environmental resources owned by the company. This research evaluates the impact of gender diversity, energy consumption, water usage, waste management, and the existence of a corporate social responsibility committee on the environmental performance of industrial companies in Indonesia listed on the Indonesian Stock Exchange during the 2018-2022 period. Using the ordinary least square method. The research results show that waste management and the existence of an environmental committee board significantly improve environmental performance. Meanwhile, energy consumption and gender diversity do not show a significant influence on environmental performance. However, the interaction between gender diversity and the corporate social responsibility committee shows a significant positive effect, indicating that the corporate social responsibility committee strengthens the positive impact of gender diversity on environmental performance. Water usage was also found to have a significant positive influence on environmental performance. These results indicate the importance of the company's commitment to sustainable environmental practices and the existence of a special committee for managing environmental issues within the board of directors.